2008
DOI: 10.1177/104063870802000408
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Biochip for Rapid Multiplex Detection of Seven Mastitis-Causing Pathogens in Bovine Milk Samples

Abstract: Abstract. To efficiently prevent and treat bovine mastitis and minimize its effect on the dairy industry, a sensitive, rapid, and specific test is required for identifying the mastitis-causing pathogens. In this study, a biochip capable of detecting 7 common species of mastitis-causing pathogens, including Corynebacterium bovis, Mycoplasma bovis, Staphylococcus aureus, and the Streptococcus spp. S. agalactiae, S. bovis, S. dysgalactiae, and S. uberis, within 6 hr was developed. The technique is based on DNA am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…It also provides an advantage of customized probe spotting. The reliability of the PVC biochip has been proven in several applications; e.g., the simultaneous detection and differentiation of seven mastitis-causing pathogens in bovine milk samples [37], Newcastle disease and avian influenza in the poultry industry [42], and Cymbidium mosaic virus , Odontoglossum ringspot virus and CaCV for orchid inspection (Dr. Orchid-3™ Kit, Dr. Chip), and the identification of insect species [43] and the sex of owls [44]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides an advantage of customized probe spotting. The reliability of the PVC biochip has been proven in several applications; e.g., the simultaneous detection and differentiation of seven mastitis-causing pathogens in bovine milk samples [37], Newcastle disease and avian influenza in the poultry industry [42], and Cymbidium mosaic virus , Odontoglossum ringspot virus and CaCV for orchid inspection (Dr. Orchid-3™ Kit, Dr. Chip), and the identification of insect species [43] and the sex of owls [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Twenty micromolar of each probe were spotted on the surface of PVC microchips with an automatic spotting machine (DR. Chip Biotechnology Inc., Miaoli, Taiwan) and immobilized by an ultraviolet crosslinker (UV Light Enterprise Co., Taichung, Taiwan) with 1.2 J for 5 min following the previous report [37]. In addition to the spots for specific tospoviruses, 100 μM of the commercial probe Anti-VP1 (Dr. Chip) was spotted for positive control of hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…Song et al (2005) reported a portable biochip system based on complementary metal oxide semiconductor (CMOS) technology that has great potential as a device for single bacteria detection. Lee et al (2008) reported a biochip, which could be a feasible tool for rapidly diagnosing mastitis causing pathogens in milk and providing information for a more effective treatment to cure mastitis. Bacillus globigii spores, which are a surrogate species for B. anthracis spores, were used as the test sample.…”
Section: Repkmentioning
confidence: 99%
“…17 Various culture-independent methods have been published for the rapid detection of mastitis pathogens in milk samples, as well as various polymerase chain reaction (PCR) approaches including real-time PCR methods. 6,15,16 A culture-independent molecular method allowing the direct detection of pathogens in clinical samples is fluorescent in situ hybridization (FISH). 24,25,29 Fluorescence-labeled oligonucleotide probes bind specific regions of the target RNA/DNA.…”
Section: Introductionmentioning
confidence: 99%